A One‐Pot Synthesis of N‐Aryl‐2‐Oxazolidinones and Cyclic Urethanes by the Lewis Base Catalyzed Fixation of Carbon Dioxide into Anilines and Bromoalkanes. Issue 30 (20th June 2016) - Niemi, Teemu; Perea‐Buceta, Jesus E.; Fernández, Israel; Hiltunen, Otto‐Matti; Salo, Vili; Rautiainen, Sari; Räisänen, Minna T.; Repo, Timo
Abstract: The multicomponent assembly of pharmaceutically relevant N ‐aryl‐oxazolidinones through the direct insertion of carbon dioxide into readily available anilines and dibromoalkanes is described. The addition of catalytic amounts of an organosuperbase such as Barton's base enables this transformation to proceed with high yields and exquisite substrate functional‐group tolerance under ambient CO2 pressure and mild temperature. This report also provides the first proof‐of‐principle for the single‐operation synthesis of elusive seven‐membered ring cyclic urethanes. Abstract : Come together : Carbon dioxide can be simultaneously fixated into anilines and primary dibromoalkanes under metal‐free ambient mild conditions to afford a broad range of N ‐aryl‐oxazolidinones or six and seven‐membered cyclic urethanes in good yields.